Управління персоналом банківської установи - Бербенець, Олена Вікторівна; Berbenets, Olena; Сичова, Маріна Олексіївна; Sychova, Marina; Таран, О. О.; Taran, O. (Чорноморський національний університет імені Петра Могили, ТОВ `ДКС Центр`, 2022)
У cтaттi досліджено поняття управління персоналом банківської установи, а також ефектив-не управління людськими ресурсами. Жодна організація неспроможна досягти своєї мети безналежного управління людськими ресурсами. Розробка концепції управління персоналоморганізації ведеться з урахуванням поточних потреб. Її складанням займаються як штатні спец-іалісти, так і залучені сторонні експерти. Дано визначення терміну "управління персоналом".Визначення широкого спектру засобів стимулювання працівників банківської установи у розрізіконцепції управління персоналом; вимог та орієнтирів, яким має відповідати система управлі-ння персоналом у банківській установі. Визначено ключові критерії управління персоналомбанку. Виявлено чинники, які впливають на процес формування циклу управління персоналомбанківської установи. The article examines the concept of personnel management of a banking institution, as well as theeffective management of human resources, one of the most important conditions for survival in acompetitive world. Personnel management is a system consisting of entities connected byorganizational and managerial relationships. Enterprise personnel is the main type of enterpriseresources. The basis of effective management is the ability to cooperate with people, therefore oneof the most important components of the bank management system is the personnel managementsubsystem. Human resource management is important for banks because banking is a serviceindustry. Human resource management and risk management are two key tasks facing banks. The ability of managers to cope with risks determines the success or failure of the banking business.Effective risk management may not be possible without an efficient and skilled workforce. In theconditions of the current financial and economic crisis, the key problem of bank personnelmanagement is the lack of an effective management system based on innovative sectors. Each bankis interested in specialists who have undergone professional training and are able to ensure theimplementation of modern banking technologies, capable of constantly improving their work methods.No organization can achieve its goal without proper management of human resources. The basis ofthe concept of personnel management are the growing role of employee's personality, knowledgeof his motivational attitudes, the ability to form and direct them according to the tasks facing theorganization. The development of the organization's personnel management concept is carried outtaking into account current needs. It is compiled by both in-house specialists and external expertsinvolved. The term "personnel management" is defined. Determination of a wide range of means ofstimulating employees of a banking institution in terms of the concept of personnel management;requirements and guidelines to which the personnel management system in the banking institutionmust meet. The key criteria of the bank's personnel management have been determined. The factorsinfluencing the process of formation of the personnel management cycle of the banking institutionwere identified.
Personnel management of the banking institut
Keywords: управління персоналом; personnel management; банківська установа; banking institution; система мотивації; motivation system; потреби; needs; концепція управління; management concept